MANAJEMEN KELEMBAGAAN DAN AKADEMIK LEMBAGA PENDIDIKAN MA’ARIF NAHDLATUL ULAMA KOTA SAMARINDA KALIMANTAN TIMUR - Abdurrahman AR; Susilo Susilo; Labulan Labulan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
The objective of this research was to identificate the Educational management and Academic quality and to doctrine the religious values to the basic Ma’arif Nahdlatul UlamaInstitute in Samarinda city East Kalimantan. This research also designed to get the object datas from the three Islamic Elementry schools which organized by Ma’arif Nahdlatul Ulama Samarinda city through many kinds ways they are : (1)Interviews The Chief of LP. Ma’arif NU, interview to three Elementry head master and other sources who bonafide informan,(2) take pictures,(3) take school’s datas or documents. The information from data collected people knewn that the Moslem Elementry School Ma’arif Nahdlatul Ulama conditions in the some ares in Samarinda city has weakness and and lackness their Institution manajement and academic manajement, because the school there hasn’t any long term program, middle term program and short term program showed to researcher as their documents. The result of datas analysis these indicate three of Moslem Elementry School Ma’arif NU those located in Samarinda city, they are MI 01 in Palaran, MI.02 Sindang Sari, MI 03 Jln. Rukun Samarinda Seberang, they were still runing slowly. The researcher’s summary in this research that, from the three of Ma’arif NU Samarinda, they’re still need high skills to construct these institutions